2014
DOI: 10.1111/nure.12097
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional influences over the life course on lean body mass of individuals in developing countries

Abstract: The double burden of childhood undernutrition and adult-onset adiposity in transitioning societies poses a significant public health challenge. The development of suboptimal lean body mass (LBM) could partly explain the link between these two forms of malnutrition. This review examines the evidence on both the role of nutrition in “developmental programming” of LBM and the nutritional influences that affect LBM throughout the life course. Studies from developing countries assessing the relationship of early nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 120 publications
(226 reference statements)
1
11
0
Order By: Relevance
“…It is encouraging that later linear and lean tissue growth did not seem to predict higher cardiometabolic risk. This may have important implications for improving quality of life through promoting growth in these components in those who had compromised early growth, because linear and lean tissue gain even in childhood is important for optimum adulthood body composition [ 29 ]. Greater length at birth and faster linear growth at all ages were related to increased current height as expected.…”
Section: Discussionmentioning
confidence: 99%
“…It is encouraging that later linear and lean tissue growth did not seem to predict higher cardiometabolic risk. This may have important implications for improving quality of life through promoting growth in these components in those who had compromised early growth, because linear and lean tissue gain even in childhood is important for optimum adulthood body composition [ 29 ]. Greater length at birth and faster linear growth at all ages were related to increased current height as expected.…”
Section: Discussionmentioning
confidence: 99%
“…This 1000 days includes 270 days of prenatal development +365 days of first postnatal year +365 days of the second postnatal year. Poor environmental conditions during this period are associated with unhealthy patterns of growth and development in later life and with higher morbidity and mortality rates in adulthood (Chandler‐Laney, Gower, & Fields, ; Gluckman, Hanson, Cooper, & Thornburg, ; Hanson & Gluckman, ; Kulkarni, Hills, & Byrne, ; Kuzawa, ; Martorell & Zongrone, ; Sayers, Singh, Mott, McDonnell, & Hoy, ; Wells, , , ).…”
Section: Introductionmentioning
confidence: 99%
“…Low birth weight has been associated with abnormalities in adult body composition, including altered fat distribution and reduced muscle mass and strength (Kulkarni et al 2014; Yliharsila et al 2007). Additionally, historical cohort studies have shown positive correlations between birth weight and muscle mass and strength throughout life (Phillips 1995; Hediger et al 1998; Kahn et al 2000; Gale et al 2001; Singhal et al 2003; Sayer et al 2004), suggesting that a reduced muscle mass may be programmed permanently by influences during intrauterine life that result in low birth weight.…”
Section: Introductionmentioning
confidence: 99%